Необыкновенные приключения Карика и Вали: [повесть] / Ян Ларри - Ларри Ян Леопольдович (Серия "Внеклассное чтение", 2007)
Экземпляры: ф. 2 (20081113) / Инвентарный номер: 92713 / Цена: 150.70 / Авт.знак: Л 25 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6